From ultra rays to astroparticles: A Historical Introduction to Astroparticle Physics - Falkenburg, Brigitte; Rhode, Wolfgang (Springer, 2012)
The book is a historical introduction to astroparticle physics. Its scope is to give an overview of this complex field of research, starting with the discovery of cosmic rays (Victor Hess, 1912) until the current experiments with particle telescopes.The book focuses on the ways in which physics changes in the course of this history. The following changes run parallel, overlap, and/orinteract: - Discovery of effects like X-rays, radioactivity, cosmic rays, new particles, the Cosmic Microwave Background and its anisotropies, but also progress through non-discoveries (monopoles) etc. - The change of the description of nature in physics, as consequence of the scientific revolutions at the beginning of the 20th century, giving rise to quantum physics, relativity, etc. - The shifts from particle physics to cosmology and to particle physics with cosmic accelerators. - The change of experimental methods, cooperations, and disciplinary divisions. With regard to the latter change, a main topic of the book is to make the specific multi-disciplinary features of astroparticle physics clear to undergraduate and graduate students, historians of physics, and philosophers of science.
Description based upon print version of record
Keywords: Geschichte; Kernastrophysik